Ascending aorta: descending thoracic aorta ratio as an additional metric to early individually oriented diagnoses of abnormalities. A non-contrast enhanced cardiac CT study. (25th November 2020) - Sosnowski, M; Czekaj, A; Brzoska, J; Chromik, K; Mlynarski, R; Tendera, M; Wojakowski, W
Abstract: Background: Coronary artery calcium (CAC) detection is the established indication for a non-contrast enhanced cardiac computed tomography (NCE-CCT). Other information, beyond CAC, can be derived from the NCE-CCT. Amongst them, data regarding thoracic aorta and its abnormalities might be of interest. Aims: We aimed at examination whether mutual proportion of ascending aorta and descending thoracic aorta diameters (AAD:DAD ratio) could be diagnostically relevant. Methods: This retrospective study included 4372 patients out of 5905 subjects undergoing NC-CCT during the last decade, in whom the thoracic aorta and pulmonary artery trunk were within common limits (AAD≤40mm, DAD<30mm, PAD<30mm). 213 persons without CVD risk factors and CAC=0 were qualified into control group (1), and 4159 patients with CVD risk factor(s) ≥1 into examined group (2) of. The range of AAD/PAD ratio normality was referenced from the group 1. In addition body mass index and CAC score were accounted for. Results: The AAD/PAD ratio in control group was 1.35±0.22 with the normal range between 1.12 and 1.57. The 90th percentile values for AAD have been established. In patients with CAC=0, amongst those with normal BMI the increased AAD:DAD ratio (>1.57), indicating high AAD, was found in 18 /43 cases with AAD>90 percentile (41.2%) and in 21/498 with normal AAD (4.2%). The respective proportions in overweight patients were 23/86 (26.7%) and 12/694 (1.7%), and in obese patients 13/67 (19.4%) and 5/397 (1.3%). In patients with CAC>0, and normal BMI the increased AAD:DAD ratio was found in 10/38 cases with AAD>90% (26.3%) and in 14/458 with normal ascending aorta size (3.1%). Proportions in overweight patients were 23/92 (25.0%) and 15/859 (1.75%), while in obese patients were 17/107 (15.9%) and 13/579 (2.2%), resp. Normal AAD:PAD ratio in patients with established AAD increase (>90 percentile), irrespective of BMI, might suggest accompanying increase in PAD. Lower AAD:PAD ratio indicated a relative increase of the DAD. Mean values of AAD and DAD in relation to BMI and CAC categories along with their ratio are presented in table 1. Conclusions: Evaluation of thoracic aorta in NC-CCT enhanced diagnostic scope of NCE-CCT. The AAD/DAD ratio, being independent of age, gender and body constitution, does not require adjustment, should be considered as additional metric for early diagnoses of thoracic aorta abnormalities well before absolute values reach the arbitrary cut-off levels. Funding Acknowledgement: Type of funding source: None